Pengaruh Budaya Organisasi Dan Komunikasi Interpersonal Terhadap Sikap Kerja Guru SMP Swasta - Elfridauli Elfridauli (Universitas Kristen Satya Wacana, 2018)
The purpose of this study is to determine the influence of organizational culture and interpersonal communication on the work attitude of private junior high school teachers in Tanjung Priok district. This research was conducted using survey method with quantitative approach and path analysis technique. The populations in this study were 307 teachers with 75 research samples of teachers selected using simple random sampling technique. Data were obtained through questionnaire and analyzed using path analysis technique. Based on the results of data analysis in this study, it can be concluded: (1) organizational culture has a direct positive influence on teacher work attitude; (2) interpersonal communication also has a positive direct effect on teacher work attitude; (3) organizational culture has a positive direct effect on interpersonal communication. Therefore, work attitude can be developed through the improvement of organizational culture and interpersonal communication.